Design of optimal digital filter and digital signal processing for a CdZnTe high resolution gamma-ray system. (August 2020) - Kim, B.J.; Lee, K.B.; Lee, J.M.; Hwang, S.H.; Heo, D.H.; Han, K.H.
Abstract: We have developed an online digital signal processing system based on an FPGA. The system consists of pile-up rejection, baseline restorer, peak detection and pole-zero cancellation for evaluation of deposited energy in the detector. The shaping algorithm employed is a Moving Window Deconvolution (MWD) to shape digitized data into a trapezoidal form. For the purpose of verification, the developed digital system was tested for 137 Cs gamma rays. The entire system is programmed using the LabVIEW environment. Highlights: An online digital signal processing system for radiation spectroscopy was developed. The Moving Window Deconvolution was adopted to shape digitized signal into a trapezoidal shape. All digital algorithms are programmed using the LabVIEW environment. The developed system was verified for gamma ray measurement with a CZT detector.